E-learning and its relationship to psychological disorders among university students - Sali, Safi Ammal; Turki, Muthana Ismaeel (Journal of Tikrit University for Humanities, 2023)
The current research aimed to identify the correlation between e-learning and psychological disorders among university students in light of the Corona pandemic, by identifying the level of use of e-learning, the level of psychological disorders, and some other demographic variables, as the current research was determined by students of Anbar University for morning study, males and females, For the scientific and humanitarian specializations, the sample size amounted to (470) male and female students, they were chosen at random, and the electronic competence scale of the researchers (Abdul Hafez& Saleh, 2022) was applied to them, which consisted of (30) items distributed over four dimensions, and a scale for mental disorders was prepared that consisted of (14) A paragraph, which was applied electronically to the research sample, after using the statistical methods (t-test) and Pearson correlation coefficient, and the results showed: the sample enjoyed a high level of using e-learning, and that they did not suffer from psychological disorders as a result of that use, and that the relationship between the two variables is weak and non-existent. Real and subject to chance, and in light of the results, the researchers presented a number of recommendations and suggestions.